Sildenafil for the treatment of necrotizing enterocolitis: an experimental study - Ipek, Sevcan; Gunes, Hatice; Yurttutan, Sadik; Tolun, Fatma; Kazanci, Ulku; Kuloglu, Tuncay; Gungor, Sukru (Walter de Gruyter Gmbh, 2022)
Backround This study was conducted to evaluate whether sildenafil effectively treats necrotizing enterocolitis (NEC). Material and Methods 38 rat pups were divided into 4 groups: control, sildenafil-control, NEC, and sildenafil-NEC (Sil-NEC). NEC was induced by hypoxia/reoxygenation and cold stress. The pups were treated by administering 1 mg/kg sildenafil by intraperitoneal injection once a day until the fourth postnatal day. The tissues were stained with hematoxylin/eosin staining and examined with the TUNEL test for apoptosis. The intestinal levels of malondialdehyde (MDA), interleukin 1 beta (IL-1 beta), inducible nitric oxide synthase (iNOS), caspase-3, and glutathione peroxidase (GSH-px) activity were quantified. Results TUNEL positivity (p=0.002) and intestinal damage grade (p<0.001) were found to be significantly lower in the Sil-NEC group. In addition, MDA, IL-1 beta, iNOS, caspase-3 levels, and GSH-px activity were also found to be significantly lower in the Sil-NEC group (p<0.001, p=0.004, p=0.011, p=0.026, p=0.002 respectively). Conclusion In this study, sildenafil has been shown to reduce intestinal damage and prevent the development of necrosis biochemically and histopathologically, with its antioxidant, anti-apoptotic, and anti-inflammatory effects, in the treatment of the experimental necrotizing enterocolitis model. This may suggest that sildenafil can be used to treat necrotizing enterocolitis, but further clinical studies are required.
Keywords: iNOS; necrotizing enterocolitis; neonate; sildenafil; TUNEL; iNOS; nekrotizan enterokolit; sildenafil; yenidogan; TUNEL